Dinamika Kewenangan Presiden Republik Indonesia Di Bidang Legislatif Pasca Perubahan Undang-Undang Dasar 1945 - Oktarina, Evi (Lex Librum : Jurnal Ilmu Hukum, 2025)
This research examines the evolution of the powers of the President of the Republic of Indonesia in the legislative field after the 1945 Constitutional Amendment. Prior to the amendment of the 1945 Constitution and the dynamics of changes in executive power towards the law-making process, this study examines the background of the following problem formulations: forms of executive authority. This kind of research is considered normative. Based on the findings, this research In terms of institution, role, authority, and position, there have been several revisions to the idea of power-sharing in Indonesia important modifications based on its growth in Indonesia. Due to its broad authority, extensive activities, and influence over other high-level state institutions, the MPR once held the highest position among all state institutions in the Republic of Indonesia until the previously mentioned changes to the 1945 Constitution. Indonesia used to have a supreme state institution, but this position was abolished through the 4th amendment to the 1945 Constitution of the Republic of Indonesia. The highest state institution now acts in accordance with the Sovereignty of the people of Indonesia contained in the 1945 Constitution of the Republic of Indonesia which functions as the highest legislation in the Republic of Indonesia and in all government institutions.